2016
DOI: 10.1093/nar/gkw939
|View full text |Cite
|
Sign up to set email alerts
|

TSTMP: target selection for structural genomics of human transmembrane proteins

Abstract: The TSTMP database is designed to help the target selection of human transmembrane proteins for structural genomics projects and structure modeling studies. Currently, there are only 60 known 3D structures among the polytopic human transmembrane proteins and about a further 600 could be modeled using existing structures. Although there are a great number of human transmembrane protein structures left to be determined, surprisingly only a small fraction of these proteins have ‘selected’ (or above) status accord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…Although cryo-electron microscopy, acknowledged by Nobel prize this year, is a promising new technique to determine the 3D structures of molecules in their natural environment ( Hite and MacKinnon, 2017 ; Nogales, 2016 ), the selection of targets for structure determination remains one of the greatest question of structural genomics experiments to better avoid long and expensive experimentation with proteins that are not likely to result in resolved structures ( Varga et al , 2017 ). TMPs are usually more challenging due to their special physical-chemical properties.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although cryo-electron microscopy, acknowledged by Nobel prize this year, is a promising new technique to determine the 3D structures of molecules in their natural environment ( Hite and MacKinnon, 2017 ; Nogales, 2016 ), the selection of targets for structure determination remains one of the greatest question of structural genomics experiments to better avoid long and expensive experimentation with proteins that are not likely to result in resolved structures ( Varga et al , 2017 ). TMPs are usually more challenging due to their special physical-chemical properties.…”
Section: Discussionmentioning
confidence: 99%
“…TMPs have very special physical-chemical properties as they span the hydrophobic cell and organelle membranes, making the determination of their structures extremely difficult. In a recent work, it was found that among the about 3000 human polytopic TMPs only around 60 ones have an experimentally determined structure that covers all of their membrane regions ( Varga et al , 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…, 2015), however, of all known protein structures only 2% belong to them (Kozma et al. , 2013) and less than a hundred human TMP non-redundant structure is determined (Varga et al. , 2017).…”
Section: Introductionmentioning
confidence: 99%
“…They are frequently targeted by pharmaceuticals: a survey found that more than 50% of marketed drugs interact with TMPs (Hopkins and Groom, 2002). Although the human proteome consists of about 25% TMPs (Dobson et al, 2015), however, of all known protein structures only 2% belong to them (Kozma et al, 2013) and less than a hundred human TMP non-redundant structure is determined (Varga et al, 2017). Knowing the structure of TMPs may aid drug development by providing targets for ligand screening and enabling the creation of models for proteins with unknown structures.…”
Section: Introductionmentioning
confidence: 99%